Fundamentals of screenwriting : the first step / Wan Aida Wan Yahaya - Wan Yahaya, Wan Aida (Fakulti Seni Persembahan & UPENA, 2004)
Screenwriting returns to its roots in an attempt to inspire young writers to write and tell their story. It is believed that good writing begins with the ability to present a story clearly, with narrative momentum and the ability to produce an emotional impact. Therefore, a few suggestions have been made to assist writers in the act of writing for the screen. However, the ability to write also depends on the writers' ability to overcome various obstacles, thus, producing a.story worthy of itself.